2009
DOI: 10.1152/ajpgi.00027.2009
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation-induced, 3′UTR-dependent translational inhibition of Hsp70 mRNA impairs intestinal homeostasis

Abstract: Although the inducible heat shock protein 70 (Hsp70) is essential for maintaining intestinal homeostasis in colitis, it is translationally downregulated in inflamed colonic mucosa, paradoxically rendering the gut more susceptible to injury. We examined the basis for this process by analyzing the role of untranslated regions (UTR) of Hsp70 mRNA in inflammation-associated downregulation in vitro and in vivo. Using luciferase-reporter assays in young adult mouse intestinal epithelial cells, we determined that cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 35 publications
2
34
1
Order By: Relevance
“…It was recently reported that adult female pigs with lower levels of F. prausnizii and branched-chain fatty acids in colon content showed a higher sensitivity of the colonic mucosa to inflammatory and oxidative stresses although HSP levels were not significantly decreased (7). These results, as well as those reported by others (3,20,39), indicate that specific commensal microbes can influence host immune compartments distinctively.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It was recently reported that adult female pigs with lower levels of F. prausnizii and branched-chain fatty acids in colon content showed a higher sensitivity of the colonic mucosa to inflammatory and oxidative stresses although HSP levels were not significantly decreased (7). These results, as well as those reported by others (3,20,39), indicate that specific commensal microbes can influence host immune compartments distinctively.…”
Section: Discussionsupporting
confidence: 87%
“…Enhanced epithelial expression of HSP70 in Crohn's disease and ulcerative colitis, independent on the degree of inflammation, has been reported (30). In contrast, more recent data show that the expression of HSPs decreased in inflammatory conditions such as IBD, indicating that they are required in maintaining intestinal homeostasis (20). In the healthy porcine gut, we found a pattern in expression of both HSP27 and HSP72 along the villus/crypt axis, with the highest expression at the surface epithelium, lowest expression in crypt cells, and limited expression in the lamina propria.…”
Section: Discussioncontrasting
confidence: 74%
“…32 The 3 0 untranslated region (3 0 -UTR)-dependent translational inhibition of HSP70 mRNA was then demonstrated in ulcerative colitis. 99 However, one study reported tissue iHSP70 protein concentrations to be higher at the time of disease diagnosis and to decrease after treatment. 100 Animal models of gut inflammation.…”
Section: Inflammatory Bowel Disease and Celiac Diseasementioning
confidence: 99%
“…INTESTINAL HEAT SHOCK PROTEINS are highly conserved, multifunctional proteins essential for maintenance of gut health, and their altered expression can render the mucosa more susceptible to sustained and severe injury and possibly malignant transformation (4,8,9,16,21,30). These proteins, particularly Hsp70 and Hsp25, are highly regulated by a complex set of extracellular cues, including gut-derived microbial signals such as LPS and short-chain fatty acids (SCFAs) (2,14,15,23,26).…”
mentioning
confidence: 99%
“…We have previously shown that this effect is in part mediated by the increased levels of proinflammatory cytokines such as interferon-␥ (IFN-␥) and tumor necrosis factor-␣ (TNF-␣) that stimulate a translational downregulation of Hsp70. These cytokines stimulate the phosphorylation of the RNA-dependent protein kinase (PKR), which in turn phosphorylates eukaryotic initiation factor-␣ (eIF-2␣), resulting in reduced Hsp70 protein translation in inflammatory bowel diseases and experimental colitis (8,9).…”
mentioning
confidence: 99%